2013
DOI: 10.1017/pasa.2012.010
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Optics Simulations for Siding Spring

Abstract: Using an observationally derived model of optical turbulence profile, we have investigated the performance of adaptive optics (AO) at Siding Spring Observatory, Australia. The simulations cover the performance for AO techniques of singleconjugate adaptive optics (SCAO), multi-conjugate adaptive optics (MCAO), and ground-layer adaptive optics (GLAO). The simulation results presented in this paper predict the performance of these AO techniques as applied to the Australian National University (ANU) 2.3-m and Angl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Simulations have shown that the instrument will be near diffraction limited with a field of view of ≈ 30" × 30" with image sampling at 0.12". 6,7 The cryostat will be designed as a generic focal plane instrument suitable for high-cadence photometry and Lucky Imaging at other observatories.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations have shown that the instrument will be near diffraction limited with a field of view of ≈ 30" × 30" with image sampling at 0.12". 6,7 The cryostat will be designed as a generic focal plane instrument suitable for high-cadence photometry and Lucky Imaging at other observatories.…”
Section: Introductionmentioning
confidence: 99%